Information systems and technology education from the university to the workplace - Lowry, Glenn R.; Turner, Rodney L.; Gale Group (Hershey, Penn. Information Science Reference, 2007)
Presents a multifaceted, global view of the human dynamics of education, supply, demand, and career development in the information systems and technology industry. Provides a tool to meet the challenges of providing improved education and employing an optimal supply of information systems and technology graduates in the decades to come.
Preface -- Acknowledgment -- A dynamic structural model of education and skills requirements for careers in information systems: perspectives across gender and time -- Leveraging diversity in information systems and technology education in the global workplace -- Critique: information systems academics' core competency? -- Enterprise systems software in the business curriculum: aligning curriculum with industry requirements -- Globalising software development in the local classroom -- Creating an entrepreneurial mindset: getting the process right for information and communication technology students -- Curriculum change and alignment with industry: the student perspective -- Aligning learning with industry requirements -- Relevance of computing programmes to industry needs in Jordan's higher education institutes professionalism and ethics: Is education the bridge? -- Experiential group learning for developing competencies in usability practice -- Industry-academic partnerships in information systems education -- Industry-university collaborations in research for information systems: an exploratory study of a management model -- Ethics for the graduating class: issues, needs, and approaches -- Tomorrow's workforce today: what is required by information systems graduates to work in a collaborative information systems workplace? -- COCA: concept-oriented course architecture towards a methodology for designing and teaching information system courses -- Enhancing the employability of ICT students with hybrid skills: insights from a UK survey with small business managers -- Teaching business intelligence in higher education -- Compilation of references -- About the contributors -- Index.
Electronic reproduction.
Keywords: Information technology -- Vocational guidance; Information technology -- Educational aspects; Electronic books